Nilai Pendidikan Karakter Dalam Film Big Brother Karya Kam Ka-Wai - Melinda Melinda; Patrisia Cuesdeyeni; Alifiah Nurachmana; Albertus Purwaka; Misnawati Misnawati (Universitas Palangka Raya, 2023)
The purpose of this study was to describe the character education values of responsibility, curiosity, hard work, respect for achievement, social care, and friendship/communicativeness in Kam Ka-Wai's Big Brother film. This study uses a descriptive qualitative approach, in which the researcher records carefully and accurately the data in the form of words, sentences, pictures, and videos contained in the film. The use of a descriptive qualitative approach in this study aims to describe the values of character education, namely responsibility, curiosity, hard work, respect for achievement, social care and communicative/friendly in the Big Brother film. The value of responsibility character education in the film Big Brother consists of 4 data. The educational value of the character of curiosity in the Big Brother film consists of 5 data. The value of hard work character education in the film Big Brother consists of 7 data. The value of character education appreciating achievement in the Big Brother film consists of 4 data. The value of social care character education in the film Big Brother consists of 12 data. The value of friendly/communicative character education consists of 4 data.